PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP LOYALITAS KARYAWAN (Studi kasus pada Kantor Jasa Penilai Publik (KJPP) Agus, Firdaus & Rekan) - Waskito, Meindro; Sari, Nur Kamila (Kinerja, 2022)
The purpose of this study is to see how work environment and compensation affect employee loyalty at KJPP Agus, Firdaus & Rekan. The sample for this study was 45 employees from KJPP Agus, Firdaus & Rekan, and the saturated samples technique was used to choose the sample non-probability sampling. The validity test, reliability test, classical assumption test, simple linear regression test, simple correlation test, coefficient of determination test, and t test were utilized to analyze the data in this study using the SPSS 25 program. According to the findings of the data analysis and hypothesis testing, the work environment variable (X1) has a positive and significant effect on the employee loyalty variable (Y) with a value of sig. 0.006 < 0.05 or tcount 2,916 > ttable 1.682. While compensation variable (X2) demonstrates a positive and significant influence on the employee loyalty variable (Y) with a sig. 0.009 > 0.05 or tcount 2,755 > ttable 1.682